A manganese phosphating coated metal magnetic powder core and preparation method thereof
By using acid manganese phosphate on the magnetic powder core to form a tight phosphate film, combined with calcination and annealing treatment, the existing problem of poor inorganic coating density is solved, and a manganese-based phosphate package with low magnetic loss and high magnetic permeability is achieved Magnetic powder core.
Patent Information
- Application Number
- CN202210500446.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-05-09
AI Technical Summary
In the existing inorganic coating method of magnetic powder core, the phosphated film has poor density, resulting in high magnetic loss and cannot effectively improve magnetic permeability and mechanical properties.
Using acid manganese phosphate as the main film-forming substance, a tight and fine phosphating film is formed by phosphating reaction of the phosphating agent solution and soft magnetic powder. Combined with calcining, pressing and annealing treatment, the thickness and density of the coating layer are regulated to prepare A manganese-based phosphated metal magnetic powder core is produced.
The manganese-based phosphated coated magnetic powder core has achieved good insulation effect, low magnetic loss, high magnetic permeability, and improved mechanical properties.
Smart Images

Figure BDA0003634691710000061 
Figure BDA0003634691710000071 
Figure BDA0003634691710000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic materials and relates to a manganese-based phosphating-coated metal magnetic powder core and a preparation method thereof. Background Art
[0002] Metal powder core is a kind of soft magnetic functional material. It is widely used in the design and production of various high-performance electronic components, such as filters, inductors, mutual inductors, chokes, etc., because of its advantages such as high saturation magnetization, relatively high magnetic permeability, relatively low coercive force and isotropy. With the increase of electronic components and the improvement of technology, higher requirements are put forward for the performance of metal powder core. Insulation coating is the most critical link in the production of powder core. It plays a decisive role in improving the resistivity of powder core and reducing high-frequency loss. Its process improvement has always been the main direction of research on the performance optimization of metal powder core.
[0003] Insulation coating can be divided into organic coating and inorganic coating according to the type of reagents. The former mainly includes polyvinyl alcohol, epoxy resin, phenolic resin, etc., which can obtain soft magnetic composite materials with good performance and low loss. As a polymer, this type of thermosetting organic resin has a high resistivity and a certain viscosity, but poor thermal stability. After high-pressure pressing and molding, the soft magnetic composite material needs a high temperature for annealing heat treatment to eliminate internal stress. High temperature may cause the organic resin insulation layer to decompose and destroy, affecting the stability of the magnetic properties of the magnetic powder core. Therefore, organically coated soft magnetic composite materials can only be applied to low-pressure pressing processes, and the density and magnetic permeability of the obtained materials are not high.
[0004] In order to overcome the defects of low heat treatment temperature of traditional organic coating, increase the heat treatment temperature of magnetic powder core, and eliminate the defects such as internal stress and dislocation generated during powder preparation and pressing, inorganic coating has gradually become the mainstream coating method. Among them, phosphate coating is one of the most commonly used inorganic coating methods in the preparation of magnetic powder core. Through in-situ passivation, an insulating layer of phosphate compounds is generated on the surface of magnetic powder to achieve the effect of inter-particle insulation. Since the lattice period of the phosphating film is consistent with that of the metal, the formed phosphating film has a strong bonding force with the base metal. At the same time, the phosphate itself has a high resistivity, and the application effect in reducing the loss of metal magnetic powder core is significant. At present, when preparing magnetic powder cores, the mainstream phosphating agents are mostly based on alkali metal phosphates as the main component, or Fe(H2PO4)2 as the main film-forming substance. Most of the phosphating films formed by these phosphating agents during coating are granular and have many pores. They cannot form a continuous and dense coating film, and the coating effect on soft magnetic powder is poor, and the loss performance of magnetic powder cores is limited. However, there is no report on coating soft magnetic powder with phosphating agent. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a manganese phosphating coated metal magnetic powder core and a preparation method thereof. The prepared manganese phosphating coated metal magnetic powder core has good insulation effect, low magnetic loss and high magnetic permeability performance.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] In a first aspect, the present invention provides a method for preparing a manganese-phosphating-coated metal magnetic powder core, comprising the following steps:
[0008] (1) preparing a phosphating agent by mixing acidic manganese phosphate, phosphoric acid, an accelerator and a complexing agent, and dissolving the phosphating agent in water to prepare a phosphating agent solution;
[0009] (2) mixing the phosphating agent solution and the soft magnetic powder to carry out a phosphating reaction, and washing and drying to obtain the coated soft magnetic powder;
[0010] (3) calcining the coated soft magnetic powder and then pressing and molding to obtain a green body;
[0011] (4) The green body is subjected to annealing heat treatment to obtain a manganese phosphating-coated metal magnetic powder core.
[0012] In the present invention, the main film-forming substance in the phosphating agent solution is acid manganese phosphate (Mn(H2PO4)2), which is deposited on the surface of the soft magnetic powder particles by phosphating reaction to form a coating layer, which is the phosphating film, and its main components are Mn3(PO4)2·3H2O and (Mn,Fe)5H2(PO4)4·4H2O. The present invention controls the thickness of the coating layer by controlling the ratio of the phosphating agent solution and the soft magnetic powder, the phosphating reaction conditions, the calcination treatment conditions, the pressing molding conditions and the annealing treatment conditions, so that the coating layer is in a compact and fine granular state, so as to prepare a manganese-based phosphating-coated metal magnetic powder core with good insulation effect, low magnetic loss, and high magnetic permeability performance.
[0013] Preferably, the mass ratio of the acid manganese phosphate, phosphoric acid, accelerator and complexing agent is acid manganese phosphate: phosphoric acid: accelerator: complexing agent = (2-6): (4-8): (2-6): (1-3).
[0014] Preferably, the mass percentage concentration of the phosphating agent in the phosphating agent solution is 0.2-4%.
[0015] In the present invention, the mass percentage concentration of the phosphating agent in the phosphating agent solution should be within an appropriate range. If the mass percentage of the phosphating agent in the phosphating agent solution is too large (>4%), the phosphating agent involved in the reaction is too much, the coating layer formed on the surface of the soft magnetic powder is too thick, and excessive non-magnetic components are introduced, resulting in a significant decrease in the magnetic permeability of the manganese phosphating-coated metal magnetic powder core; if the mass percentage of the phosphating agent in the phosphating agent solution is too low (<0.2%), the phosphating agent involved in the reaction is too little, the coating layer formed on the surface of the soft magnetic powder is very thin, and the coating layer has poor density, resulting in poor magnetic properties of the manganese phosphating-coated metal magnetic powder core.
[0016] Preferably, the acid manganese phosphate is prepared by the following method:
[0017] The phosphoric acid solution and manganese are mixed and dissolved until the metal manganese is completely dissolved, and then dried to obtain acid manganese phosphate; PO4 in the phosphoric acid solution 3- The molar ratio of manganese is (2-5):1.
[0018] Preferably, the promoter includes at least one of manganese nitrate, manganese nitrite, hydrogen peroxide, molybdate, and nitro compound.
[0019] Preferably, the complexing agent includes at least one of citric acid, tartaric acid, salicylic acid and succinic acid.
[0020] Preferably, the mass ratio of the phosphating agent solution to the soft magnetic powder is (5-20):1.
[0021] Preferably, the soft magnetic powder includes at least one of pure iron powder, carbonyl iron powder, iron-silicon alloy powder, iron-silicon-aluminum alloy powder, iron-nickel alloy powder, iron-nickel-molybdenum alloy powder, iron-based amorphous alloy powder and iron-based nanocrystalline alloy powder.
[0022] Preferably, the phosphating reaction is carried out at a temperature of 50 to 95° C. and for a time of 5 to 45 minutes.
[0023] In the present invention, the temperature of the phosphating reaction should not be lower than 50°C. If the temperature is lower than 50°C, the reaction rate is too slow, the density of the coating layer is poor, and there are too many pores, which makes the soft magnetic powder inside easy to be oxidized, thereby reducing the magnetic permeability of the manganese phosphating coated metal magnetic powder core. The inventors have found through a large number of experimental studies that the time of the phosphating reaction should be within an appropriate range. If the reaction time is less than 5 minutes, the phosphating reaction is insufficient and the effect of completely coating the soft magnetic powder cannot be achieved, resulting in the deterioration of the magnetic properties of the magnetic powder core; if the phosphating reaction time is greater than 45 minutes, the reaction time is too long, and the soft magnetic powder reacts under the action of phosphoric acid to generate more and more ferrous ions, resulting in a decrease in the magnetic permeability of the manganese phosphating coated metal magnetic powder core.
[0024] Preferably, the drying temperature is 70-90° C. and the drying time is 0.5-2 h.
[0025] Preferably, the calcination treatment environment is any one of a vacuum environment and an inert atmosphere environment.
[0026] More preferably, the inert atmosphere is at least one of nitrogen and argon.
[0027] Preferably, the calcination temperature is 200-500° C. and the time is 0.2-1 h. In the present invention, the coated soft magnetic powder is calcined to remove the crystal water in the powder.
[0028] Preferably, the molding pressure of the compression molding is 800-1200 MPa, and the holding time is 5-15 s.
[0029] In the present invention, if the molding pressure is less than 800 MPa, the green body is not dense during pressing, resulting in poor mechanical properties of the manganese phosphating coated metal magnetic powder core; if the molding pressure is greater than 1200 MPa, the pressing pressure is too high, which can easily cause cracks on the green body surface.
[0030] Preferably, the annealing heat treatment is performed in an environment of a vacuum environment or an inert atmosphere environment.
[0031] More preferably, the inert atmosphere is at least one of nitrogen and argon.
[0032] Preferably, the annealing heat treatment is performed at a temperature of 200 to 500° C. and for a time of 1 to 3 hours.
[0033] The present invention performs annealing heat treatment on the green body at 200-500°C for 1-3h, which can effectively promote grain growth, eliminate grain boundaries, and eliminate residual stress, thereby reducing the magnetic loss of the metal magnetic powder core, and is also beneficial to improving the mechanical properties of the metal magnetic powder core. Studies have found that the temperature of the annealing heat treatment has a great influence on the performance of the metal magnetic powder core. When the temperature of the annealing heat treatment is lower than 200°C, the annealing heat treatment cannot effectively eliminate the residual stress, resulting in an increase in the magnetic loss of the metal magnetic powder core and a decrease in the mechanical properties; when the temperature of the annealing heat treatment is higher than 500°C, the temperature is too high, the phosphate in the coating layer decomposes, causing the coating layer to rupture, which significantly increases the magnetic loss of the metal magnetic powder core.
[0034] In a second aspect, the present invention provides a manganese-phosphating-coated metal magnetic powder core, which is prepared by the preparation method of the manganese-phosphating-coated metal magnetic powder core as described in the first aspect.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The present invention prepares a phosphating agent solution, and the phosphating agent is reacted and deposited on the surface of the soft magnetic powder to generate an insulating coating layer, and the formed coating layer is in a compact and fine granular state; the present invention utilizes the phosphating agent to perform phosphating deposition on the surface of the soft magnetic powder, and the film formation is easy and has the characteristics of adjustable uniformity. The coated soft magnetic powder is subjected to calcination treatment, compression molding, and annealing heat treatment to successfully prepare a manganese-based phosphating-coated metal magnetic powder core. The prepared manganese-based phosphating-coated metal magnetic powder core has good insulation effect, low magnetic loss, and maintains high magnetic permeability characteristics. DETAILED DESCRIPTION
[0037] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0038] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0039] Example 1
[0040] This embodiment provides a method for preparing a manganese-phosphating-coated metal magnetic powder core, comprising the following steps:
[0041] (1) Deionized water and phosphoric acid were mixed to prepare a phosphoric acid solution with a mass percentage concentration of 25%. 3- The molar ratio of phosphoric acid to metallic manganese is 4:1, the phosphoric acid solution and the metallic manganese are mixed and stirred until the metallic manganese is completely dissolved, and then the solution is evaporated to dryness at 60° C. to remove water to obtain acid manganese phosphate for later use; the acid manganese phosphate, phosphoric acid, manganese nitrate and citric acid are mixed in a mass ratio of 3:3:1:1 to obtain a phosphating agent, and the phosphating agent is dissolved in deionized water to prepare a phosphating agent solution, wherein the mass percentage concentration of the phosphating agent in the phosphating agent solution is 0.5%;
[0042] (2) Add 50 g of carbonyl iron powder to 250 mL of the phosphating agent solution, stir and react at 90° C. and 400 r / min for 5 min, then wash with 250 mL of deionized water for 10 min, discard the supernatant after washing, wash with 250 mL of anhydrous ethanol for 10 min, discard the supernatant after washing, and then place in a vacuum drying oven and dry at 80° C. for 1 h to obtain metal magnetic powder;
[0043] (3) placing the metal magnetic powder in a tubular furnace and calcining it at 300° C. for 0.5 h under nitrogen protection to remove the crystal water inside the powder, and then pressing it into a shape with a molding pressure of 800 MPa and a holding time of 10 s to obtain a ring-shaped green body;
[0044] (4) The annular green body is placed in a tubular furnace and annealed at 500° C. for 1 h under nitrogen protection to obtain a metal magnetic powder core coated with manganese phosphating.
[0045] The magnetic loss and magnetic permeability of the manganese phosphating coated metal magnetic powder core of this embodiment are tested. The magnetic loss and magnetic permeability are data obtained by testing at 50mT / 100KHz.
[0046] The test results show that in this embodiment, the magnetic loss of the manganese phosphating coated metal magnetic powder core is 372.11mW / cm 3 , the magnetic permeability is 73.569.
[0047] Embodiments 2 to 5
[0048] Examples 2 to 5 respectively provide a manganese phosphating-coated metal magnetic powder core, and the preparation method thereof is different from that of Example 1 in that the mass percentage concentration of the phosphating agent in the phosphating agent solution is as shown in Table 1. In order to explore the effect of the mass percentage concentration of the phosphating agent in the phosphating agent solution on the performance of the manganese phosphating-coated metal magnetic powder core, the prepared manganese phosphating-coated metal magnetic powder core is subjected to magnetic loss and magnetic permeability tests, and the test conditions are: Bm=50mT, f=100KHz; the test results are shown in Table 1.
[0049] Table 1
[0050]
[0051] The test results show that the mass percentage concentration of the phosphating agent in the phosphating agent solution is preferably less than 4%. When the mass percentage concentration of the phosphating agent in the phosphating agent solution is higher than 4%, the formed phosphating film is too thick, resulting in an increase in the content of non-magnetic substances in the prepared manganese-based phosphating-coated metal magnetic powder core and a decrease in magnetic properties.
[0052] Embodiments 6 to 12
[0053] Examples 6 to 12 respectively provide a manganese phosphating-coated metal magnetic powder core, and the preparation method thereof is different from that of Example 1 in that the phosphating reaction time is as shown in Table 2. In order to explore the influence of the phosphating reaction time on the performance of the manganese phosphating-coated metal magnetic powder core, the prepared manganese phosphating-coated metal magnetic powder core is subjected to magnetic loss and magnetic permeability tests, and the test conditions are: Bm=50mT, f=100KHz; the test results are shown in Table 2.
[0054] Table 2
[0055]
[0056] The test results show that the phosphating reaction time is preferably 5 to 45 minutes. When the phosphating reaction time is less than 5 minutes, the phosphating reaction is incomplete, the phosphating film is poorly bonded to the substrate, and a large amount of phosphate is washed away during the rinsing process, resulting in a sharp increase in the loss of the prepared manganese-based phosphating-coated metal magnetic powder core; when the phosphating reaction time is higher than 45 minutes, the phosphating reaction is excessive, and a large amount of substrate powder participates in the reaction and is oxidized to Fe 2+ , which leads to the deterioration of the magnetic properties of the prepared manganese phosphating-coated metal magnetic powder core.
[0057] Embodiments 13 to 16
[0058] Examples 13 to 16 respectively provide a metal magnetic powder, and the preparation method thereof is different from that of Example 1 in that the phosphating reaction temperature is as shown in Table 3. In order to explore the influence of the phosphating reaction temperature on the performance of the manganese phosphating-coated metal magnetic powder core, the prepared manganese phosphating-coated metal magnetic powder core is subjected to magnetic loss and magnetic permeability tests. The test conditions are: Bm=50mT, f=100KHz; the test results are shown in Table 3.
[0059] Table 3
[0060]
[0061] The phosphating reaction is accompanied by a large amount of heat absorption. The temperature rise can accelerate the reaction rate and form a denser phosphating film. The test results show that when the temperature is lower than 50℃, the reaction is difficult to proceed, a complete phosphating film cannot be formed, and the magnetic properties are poor.
[0062] Embodiments 17 to 19
[0063] Examples 17 to 19 respectively provide a metal magnetic powder, and the preparation method thereof is different from that of Example 1 in that the temperature of the annealing heat treatment is as shown in Table 4. In order to explore the effect of the temperature of the annealing heat treatment on the performance of the manganese phosphating-coated metal magnetic powder core, the prepared manganese phosphating-coated metal magnetic powder core was tested for magnetic loss and magnetic permeability, and the test conditions were: Bm=50mT, f=100KHz; the test results are shown in Table 4.
[0064] Table 4
[0065]
[0066] Annealing heat treatment can eliminate the residual stress generated during the pressing process and reduce the hysteresis loss of the magnetic powder core. The test results show that appropriately increasing the annealing temperature helps to improve the magnetic properties of the magnetic powder core, but when the temperature reaches 600°C, the phosphating film begins to decompose and the magnetic properties deteriorate.
[0067] Embodiments 20 to 23
[0068] Examples 20 to 23 respectively provide a magnetic powder core, and the preparation method thereof is different from that of Example 1 in that the volume of the phosphating agent solution and the mass of the soft magnetic powder are shown in Table 5. In order to explore the effect of the addition amount of the phosphating agent solution and the soft magnetic powder on the performance of the manganese phosphating-coated metal magnetic powder core, the prepared manganese phosphating-coated metal magnetic powder core was tested for magnetic loss and magnetic permeability, and the test conditions were: Bm=50mT, f=100KHz; the test results are shown in Table 5.
[0069] Table 5
[0070]
[0071] Embodiments 24 to 31
[0072] Embodiments 24 to 31 respectively provide a magnetic powder core, and the preparation method thereof is different from that of Embodiment 1 in that the mass ratios of acid manganese phosphate, phosphoric acid, manganese nitrate, and citric acid in the phosphating agent solution are shown in Table 6. In order to explore the influence of the addition amount of the phosphating agent solution and the soft magnetic powder on the performance of the manganese phosphating-coated metal magnetic powder core, the prepared manganese phosphating-coated metal magnetic powder core was tested for magnetic loss and magnetic permeability, and the test conditions were: Bm=50mT, f=100KHz; the test results are shown in Table 6.
[0073] Table 6
[0074]
[0075] Comparative Example 1
[0076] This comparative example provides a metal magnetic powder core, and its preparation method comprises the following steps:
[0077] (1) Phosphate solution is prepared with phosphoric acid and acetone, wherein the mass percentage concentration of phosphoric acid in the phosphate solution is 2%.
[0078] (2) Add 50 g of carbonyl iron powder to 250 mL of the phosphating agent solution, stir and react for 15 min at room temperature and 200 r / min, wash with 250 mL of anhydrous ethanol for 10 min, discard the supernatant after washing, and then place in a vacuum drying oven and dry at 80° C. for 1 h to obtain metal magnetic powder;
[0079] (3) placing the metal magnetic powder in a tubular furnace and calcining it at 300° C. for 0.5 h under nitrogen protection, and then pressing it into a shape with a molding pressure of 800 MPa and a holding time of 10 s to obtain a ring-shaped green body;
[0080] (4) The annular green body is placed in a tubular furnace and annealed at 500°C for 2 h under nitrogen protection to obtain a metal magnetic powder core.
[0081] The magnetic loss and magnetic permeability of the metal magnetic powder core of this comparative example were tested. The magnetic loss and magnetic permeability were the data obtained by testing under the condition of 50mT / 100KHz.
[0082] The test results show that the magnetic loss of the prepared metal magnetic powder core is 439.61mW / cm 3 , the magnetic permeability is 48.122.
[0083] The test data of Example 1 and Comparative Example 1 can be compared to show that the manganese-based phosphating-coated metal magnetic powder core prepared by the preparation method described in the present invention has low magnetic loss and better magnetic permeability performance. In Comparative Example 1, during the phosphating reaction, the soft magnetic powder generates a passivation film with Fe(H2PO4)2 as the main component under the action of phosphoric acid, but is limited by the properties of the passivation film itself, and the improvement of the magnetic loss performance of the metal magnetic powder core is limited. Different from this, Example 1 mainly uses Mn(H2PO4)2 as the main film-forming material, which can form a continuous and dense coating layer on the surface of the soft magnetic powder, which can significantly improve the magnetic loss performance of the metal magnetic powder core while maintaining high magnetic permeability characteristics.
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a manganese-phosphating-coated metal magnetic powder core, characterized in that: The steps include: (1) preparing a phosphating agent by mixing acidic manganese phosphate, phosphoric acid, an accelerator and a complexing agent, and dissolving the phosphating agent in water to prepare a phosphating agent solution; (2) mixing the phosphating agent solution and the soft magnetic powder to carry out a phosphating reaction, and washing and drying to obtain the coated soft magnetic powder; (3) calcining the coated soft magnetic powder and then pressing and molding to obtain a green body; (4) performing annealing heat treatment on the green body to obtain a manganese phosphating-coated metal magnetic powder core; The mass ratio of the acid manganese phosphate, phosphoric acid, accelerator and complexing agent is acid manganese phosphate: phosphoric acid: accelerator: complexing agent = (2-6): (4-8): (2-6): (1-3); The mass percentage concentration of the phosphating agent in the phosphating agent solution is 0.2 to 4%; The mass ratio of the phosphating agent solution to the soft magnetic powder is (5-20):1; The preparation method of the acid manganese phosphate is as follows: mixing and dissolving a phosphoric acid solution and manganese until the metal manganese is completely dissolved, and drying to obtain the acid manganese phosphate; the PO4 3- The molar ratio of manganese is (2-5):1; The complexing agent includes at least one of citric acid, tartaric acid, salicylic acid and succinic acid.
2. The method for preparing the manganese phosphating coated metal magnetic powder core according to claim 1, characterized in that: The soft magnetic powder includes at least one of pure iron powder, carbonyl iron powder, iron-silicon alloy powder, iron-silicon-aluminum alloy powder, iron-nickel alloy powder, iron-nickel-molybdenum alloy powder, iron-based amorphous alloy powder and iron-based nanocrystalline alloy powder.
3. The method for preparing the manganese phosphating coated metal magnetic powder core according to claim 1, characterized in that: The temperature of the phosphating reaction is 50-95° C. and the time is 5-45 minutes.
4. The method for preparing a manganese phosphating-coated metal magnetic powder core according to claim 1, characterized in that: The calcination treatment is carried out at a temperature of 200 to 500° C. and for a time of 0.2 to 1 h.
5. The method for preparing the manganese phosphating coated metal magnetic powder core according to claim 1, characterized in that: The molding pressure of the compression molding is 800-1200 MPa, and the holding time is 5-15 s.
6. The method for preparing the manganese phosphating coated metal magnetic powder core according to claim 1, characterized in that: The annealing heat treatment is performed under vacuum or inert atmosphere, the temperature of the annealing heat treatment is 200-500° C., and the time is 1-3 hours.
7. A manganese phosphating coated metal magnetic powder core, characterized in that: The magnetic powder core is prepared by the method for preparing a manganese-phosphating-coated metal magnetic powder core according to any one of claims 1 to 6.
